UTILIZING KAHOOT! IN VOCABULARY TEACHING FOR STUDENTS WITH SPECIAL NEEDS - Anandha Anandha; Dini Anggraheni; Adiprana Yogatama (English Language and Literature International Conference (ELLiC) Proceedings, 2021)
This research purpose is to enhance the English ability of Students with Special Needs in learning English vocabulary. The use of online learning media now was needed especially on distance learning in which Schooling from Home is the only choice during the pandemic era. The use of Kahoot! meet the needs of online teaching-learning activity. The research subjects were an English club in SLB D YPAC Semarang. The descriptive qualitative method was used in this research. The research result is the English ability enhancement in gaining the new vocabularies. The result is satisfying, students of SLB D YPAC Semarang were highly motivated in using Kahoot! Because they can directly see the winner podium. The final conclusion stated that utilizing Kahoot! Could enhance the English vocabulary for Students with Special Needs.